Peran Teknologi Finansial dalam Mengubah Pola Bisnis dan Sistem Ekonomi Global Kontemporer - Yustina Siagian; Viony Natasya Napitupulu; Tanti Sitompul; Jeremy Sitorus; Hamonangan Siallagan (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study examines the role of financial technology (fintech) in transforming business models and the contemporary global economic system. The rapid development of fintech has driven significant changes in the financial sector through innovations in digital payment systems, technology-based financing, online investment platforms, and the use of artificial intelligence and big data analytics. These developments have not only improved operational efficiency and accessibility of financial services but have also shifted conventional business models toward more digital, inclusive, and competitive ecosystems. This research employs a literature review method by analyzing scientific journals, institutional reports, and relevant publications related to fintech and the global economy. The findings indicate that fintech contributes to increased financial inclusion, accelerates cross-border transaction flows, and supports the integration of global financial markets. However, the expansion of fintech also presents new challenges, including data security risks, regulatory disparities among countries, and potential disruptions to traditional financial institutions. Therefore, adaptive and collaborative regulatory frameworks are essential to ensure that fintech development supports the stability and sustainability of the global economic system. This study is expected to provide insights for academics, policymakers, and practitioners in understanding the dynamic role of fintech in the modern global economy.